Effectiveness of the Garces Model in Evaluating Grammatical Efficiency; Case Study: Ali Shirvani\'s Translation of Nahj al-Balagheh [In Persian] - Mahin Hajizadeh; Rahna Farhadi (زبان کاوی کاربردی, 2023)
The translation of religious writings is one of the most challenging and exact forms of translation, requiring the translator to be more accurate and skilled to express the literary nuances of the subject text. However, to assess the accuracy and quality of these translations, fidelity or lack thereof to the original text, level of quality and acceptability, etc., one must inevitably refer to the theories proposed in the field of translation criticism and evaluation. Only then can these translations be properly assessed. The Garces model, one of these models, is employed to assess how well literary materials have been translated. The four levels of semantic-lexical, syntactic-word construction, discourse-functional, and stylistic-practical level are proposed in this model to compare the similarity between the source text and the target text. Based on these four levels, it evaluates the quality and acceptability of the translated texts. As a result, the current study uses a descriptive-analytical approach to assess the accuracy and acceptability of Ali Shirvani's translation of Nahj al-Balagheh based on Garces's theory. The findings demonstrate that Shirvani is content-oriented in her translation and frequently clarifies and broadens the meaning of Imam Ali's statements based on the positive, negative, and neutral strategies that are suggested in the Garces model. The second and fourth layers of the Garces pattern, out of its four levels, are most frequently translated by Shirvani. He occasionally employs constructive strategies like syntactic expansion, grammatical or syntax changes, viewpoint shifts, etc. On the other side, there are also issues with his translation that detract from its quality, such as omissions, translation errors, verbosity, etc.